Cosmological and astrophysical structures in the Einstein-de Sitter universe (2006)
In this work we explore the consequences of a non zero cosmological constant on cosmological and astrophysical structures. We find that the effects are associated to the density of the configurations as well as to the geometry. Homogeneous and spherical configurations are slightly affected. For non homogeneous configurations, we calculate the effects on a polytropic configurations and on the isothermal sphere, making special emphasis on the fact that the cosmological constant sets certain scales of length, time, mass and density. Sizable effects are determined for non spherical systems, as elliptical galaxies or galactic clusters, where the effects of A are increased as long as the configurations deviates from spherical symmetry, i.e, for flat systems. The equilibrium of rotating ellipsoids are modified and the cosmological constant allows new configurations in equilibrium. Finally we explore the motion of a test particle in the Schwarszchild- de Sitter space time and set astrophysical bounds for the cosmological constant, not only from the Newtonian limit, but also from a full general relativistic analysis.